Prognostic value of white matter lesion shrinking in early multiple sclerosis: An intuitive or naïve notion? - Pongratz, Viola (Brain Behav, 2019)
BACKGROUND AND PURPOSE: New or enlarging T2‐hyperintense white matter lesions (WML) are associated with clinical disease progression in multiple sclerosis (MS). The prognostic value of WML shrinking is unclear. Assuming that waning of acute inflammation and repair processes would be the main drivers of WML shrinking, we aimed to assess the prognostic value of WML shrinking in early MS. METHODS: We retrospectively analyzed a cohort of 144 early MS patients with three brain MRI scans at baseline and after 1 and 3 years available. All patients were therapy naïve at baseline and 70.5% of them treated with disease modifying drugs at year 1. We determined the volume of WML shrinking between MRI scans, total WML volumes, number of gadolinium‐enhancing and new WML, white matter (WM) and gray matter volumes at each MRI scan. Clinical disability was measured by Expanded Disability Status Scale. We performed the correlation analyses of WML shrinking with other MRI parameters and clinical outcome. RESULTS: White matter lesions shrinking was highly variable between patients and correlated with the initial number of gadolinium‐enhancing WML and with WM volume decrease. WML shrinking was not associated with clinical outcome. CONCLUSION: We found no indication of a prognostic value of WML shrinking in early MS patients. WML shrinking seems to be related to waning of acute inflammation.